The Sage encyclopedia of the Internet - Warf, Barney, 1956- (Sage Publications Ltd., 2018)
The Internet needs no introduction, and its significance today can hardly be exaggerated. Today, more people are more connected technologically to one another than at any other time in human existence. For a large share of the world's people, the Internet, text messaging, and various other forms of digital social media such as Facebook have become thoroughly woven into the routines and rhythms of daily life. The Internet has transformed how we seek information, communicate, entertain ourselves, find partners, and, increasingly, it shapes our notions of identity and community. The SAGE Encyclopedia of the Internet addresses the many related topics pertaining to cyberspace, email, the World Wide Web, and social media. Entries will range from popular topics such as Alibaba and YouTube to important current controversies such as Net neutrality and cyberterrorism. The goal of the encyclopedia is to provide the most comprehensive collection of authoritative entries on the Internet available, written in a style accessible to academic and non-academic audiences alike.